SISTEM MANAJEMEN PENDIDIKAN ISLAM DAN MADRASAH SEBAGAI LEMBAGA PENDIDIKAN - Muhammad Zamzam; Zaimudin Zaimudin (Roqooba Journal of Islamic Education Management, 2022)
Islamic Education as a subsystem in National Education, has a strategic role to achieve the goals of National Education. In three decades, Islamic education has made a good contributionto education in Indonesia. As a consequence of an open attitude in management, to decide on an agreement in deliberation, everyone will be responsible and have a commitment to making the agreement. Efforts to implement Islamic education in accordance with our vision need several tactical methods. Islamic Education Councils such as Madrasahs must first change the management system. In this case, Madrasah leaders must have good vision, responsibility, knowledge, and managerial skills. Islamic education in Indonesia is a legacy of Islamic civilization and at the same time an asset for the development of national education. As a legacy, it is a historical mandate to be preserved and developed by Muslims from time to time. Meanwhile, as an asset, Islamic education spread across various regions opens up opportunities for the Indonesian people to organize and manage it, in accordance with the national education system.